KONTRIBUSI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KECERDESAN EMOSIONAL DAN SPIRITUAL PESERTA DIDIK DI MADRASAH ALIYAH Al BAROKAH - Sodik, Muhammad; Jadid Khadavi, M. (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
The aim of this research is to determine the contribution of PAI teachers in developing emotional intelligence (EQ) and spiritual intelligence (SQ) of MA al-Barokah students and to determine the factors that can influence it. The research is classified as case study research with a qualitative approach. Data collection carried out by researchers was through observation and interviews. The informants in this research consisted of: Principal, Deputy Head for Curriculum, Deputy Head for Student Affairs, PAI Teacher, and Students. The results of this research show that the contribution of PAI teachers in developing students' emotional and spiritual intelligence at MA al-Barokah is manifested in the preparation of learning programs, program implementers as well as role models. The form of development carried out by the institution is to provide guidance, direction, advice and constant learning motivation (istiqamah) to students through learning program policies that are oriented towards emotional and spiritual development.